1964
DOI: 10.1090/s0025-5718-1964-0165668-2
|View full text |Cite
|
Sign up to set email alerts
|

Laguerre’s method applied to the matrix eigenvalue problem

Abstract: 1. Introduction. We present a new algorithm for the calculation of the eigenvalues of real square matrices of orders up to 100. The basic method is directly applicable to complex matrices as well and, in both cases, with each eigenvalue X of A a vector v is produced for which (A -XI)v is null except for a small last element. This vector is not always an approximation to the eigenvector for X and this algorithm claims only to find eigenvalues.The main concern has been to use only single precision arithmetic alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0

Year Published

1974
1974
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 10 publications
0
50
0
Order By: Relevance
“…Hyman's method, which constitutes the basis for our work, is the best of the latter for its simplicity, efficiency, stability, and accuracy. It was effectively used by Parlett [13] with Laguerre's iteration to produce eigenvalue solvers outperformed only by their QR competitors. While it is generally thought of as a scalar algorithm, its extension to the vector form (2.4) is straight-forward, as demonstrated below.…”
Section: The Direct Evaluation Of the Shift Vectormentioning
confidence: 99%
“…Hyman's method, which constitutes the basis for our work, is the best of the latter for its simplicity, efficiency, stability, and accuracy. It was effectively used by Parlett [13] with Laguerre's iteration to produce eigenvalue solvers outperformed only by their QR competitors. While it is generally thought of as a scalar algorithm, its extension to the vector form (2.4) is straight-forward, as demonstrated below.…”
Section: The Direct Evaluation Of the Shift Vectormentioning
confidence: 99%
“…To obtain the natural frequencies and natural modes, we are interested in ecuation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) in the absence of a forcing function, i.e., where v, denotes the natural mode vector corresponding to a pole of multiplicity in.,.…”
Section: IImentioning
confidence: 99%
“…A simple method known as Fourier stability analysis may be used to determine the stability criterion for an uncom-* pressed difference scheme (e.g., equation (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) or (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) instead of equation (3-29) …”
Section: IImentioning
confidence: 99%
“…[6][7][8]17,22]. A number of numerical experiments have shown that convergence breakdown is extremely rare solving polynomial equations, making this method very close to being globally convergent.…”
Section: Introductionmentioning
confidence: 99%
“…A number of numerical experiments have shown that convergence breakdown is extremely rare solving polynomial equations, making this method very close to being globally convergent. Extensive studies of Laguerre's method can be found in [9,13,16] (see, also, [4,8,12,17,18,20]). …”
Section: Introductionmentioning
confidence: 99%